ANALISIS KEBUTUHAN E-LKPD FISIKA BERBASIS DUAL SPACE INQUIRY FRAMEWORK UNTUK MENSTIMULUS KEMAMPUAN BERPIKIR KRITIS SISWA - Azizah, Izzati; Novitra, Fuja; Fauzi, Ahmad; Riyasni, Selma (Jurnal MIPA dan Pembelajarannya, 2025)
This research explores the necessity for developing a physics-based Electronic Student Worksheet (E-LKPD) integrated with the Dual Space Inquiry Framework (DSIF), aimed at enhancing students' critical thinking abilities within the topic of heat. Conducted at the define phase of the 4D model (Define, Design, Develop, Disseminate), the study encompasses a series of analyses: front-end, learner, task, concept, and instructional objectives specification. Data were obtained through a combination of literature review, classroom observations, structured interviews, and questionnaires involving a physics teacher and 32 students at SMA Negeri 3 Bukittinggi. The results reveal a significant demand from both educators and learners for engaging, inquiry-based digital learning tools such as DSIF-based E-LKPDs to improve the quality of physics instruction, especially in the heat topic.